2021
DOI: 10.3389/fmicb.2021.611798
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Pressure, N2/CO2 Atmosphere Is Suitable for Cyanobacterium-Based Life-Support Systems on Mars

Abstract: The leading space agencies aim for crewed missions to Mars in the coming decades. Among the associated challenges is the need to provide astronauts with life-support consumables and, for a Mars exploration program to be sustainable, most of those consumables should be generated on site. Research is being done to achieve this using cyanobacteria: fed from Mars's regolith and atmosphere, they would serve as a basis for biological life-support systems that rely on local materials. Efficiency will largely depend o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 66 publications
0
43
0
Order By: Relevance
“…support systems (Gòdia et al, 2002;Wheeler, 2017) and a Martian atmosphere has been shown to support such biological systems (Verseux et al, 2021). While plant-based food has been the main staple considered for extended missions (Drake et al, 2010;Anderson et al, 2018;Cannon and Britt, 2019), the advent of cultured and 3D printed meat-like products from animal, plant and fungal cells may ultimately provide a scalable and efficient alternative to cropping systems (Cain, 2005;Pandurangan and Kim, 2015;Hindupur et al, 2019).…”
Section: Food and Pharmaceutical Synthesismentioning
confidence: 99%
“…support systems (Gòdia et al, 2002;Wheeler, 2017) and a Martian atmosphere has been shown to support such biological systems (Verseux et al, 2021). While plant-based food has been the main staple considered for extended missions (Drake et al, 2010;Anderson et al, 2018;Cannon and Britt, 2019), the advent of cultured and 3D printed meat-like products from animal, plant and fungal cells may ultimately provide a scalable and efficient alternative to cropping systems (Cain, 2005;Pandurangan and Kim, 2015;Hindupur et al, 2019).…”
Section: Food and Pharmaceutical Synthesismentioning
confidence: 99%
“…Both approaches have trade-offs in terms of equivalent system mass (Bugbee et al, 2020), and either further complicates the already complex design of photobioreactors (Johnson et al, 2018). If footprint and productivity constraints are relaxed (considering semi-open cultivation-systems like domed and pressurized ponds instead of photobioreactors), however, it is a straight forward way to generate initial biomass, which can serve as foundation for further biology (Billi et al, 2021;Verseux et al, 2021). Light-independent, lithoautotrophy can fix carbon by relying on chemically provided reducing power.…”
Section: From Autotrophy To Heterotrophy-impact On Process Parameters and Complexitymentioning
confidence: 99%
“…For production of biomass, the diazotrophic and spore-forming cyanobacterium species Anabaena, which is tolerant to Mars-like growth-conditions (Verseux et al, 2021), holds great promise. Synechocystis sp.…”
Section: Organisms With High Potential For Bio-isru On Marsmentioning
confidence: 99%
“…Verseux et al performed an investigation into the ability of Anabaena sp. to grow on a simulated regolith as well as in a controlled atmosphere of 96% N 2 and 4% CO 2 [ 26 ]. Their findings showed “vigorous growth” with the simulated conditions with an atmospheric pressure of only 100 hPa.…”
Section: Habitat Alsmentioning
confidence: 99%
“…Further, they also analyzed the biomass resulting from the Anabaena sp. growth and deemed it was a viable substrate for other BLSS modules to be employed due to its use by strains of E. coli [ 26 ]. The growth of E. coli using the Anabaena sp.…”
Section: Habitat Alsmentioning
confidence: 99%